Size Matters: Unequal Gains Among Micro, Small, and Medium Enterprises in Public Contracts - Peter Nemec (SAGE Open)
Micro, small, and medium-sized enterprises (MSMEs) are pivotal to economic growth, employment generation, and fostering innovation. Despite their critical role and significant representation in the EU economy, MSMEs face persistent challenges in accessing public procurement opportunities, often due to limited resources and the complexities of procurement regulations. Although policies to foster MSME in the public contract domain are well-acknowledged, empirical evidence regarding their effectiveness across different firm sizes remains inconclusive. Recognising the heterogeneity of MSMEs, this study investigates the impact of MSME-friendly procurement practices on their success, accounting for the diverse firm’s aspects such as size, age, and sector within which they operate. Utilising procurement data from Slovakia spanning 2016 to 2020, the analysis uncovers nuanced effects of measures such as contract allotment, best price-quality evaluation criteria, and geographical proximity to contracting authorities across individual MSME size subcategories. The findings reveal that while micro-enterprises benefit significantly from these practices, the advantages for small and medium-sized enterprises are comparatively limited. This study underscores the need to tailor procurement policies to different MSME size categories’ distinct needs and capacities to enhance their participation and success in public procurement markets. JEL Classification: H57, L25, O38.